Molecular Characterization of a Novel Polymycovirus From Penicillium janthinellum With a Focus on Its Genome-Associated PASrp - Sato, Yukiyo; Jamal, Atif; Kondo, Hideki; Suzuki, Nobuhiro (Frontiers in Microbiology, 2020)
The genus Polymycovirus of the family Polymycoviridae accommodates fungal RNA viruses with different genomic segment numbers (four, five, or eight). It is suggested that four members form no true capsids and one forms filamentous virus particles enclosing double-stranded RNA (dsRNA). In both cases, viral dsRNA is associated with a viral protein termed "proline-alanineserine-rich protein" (PASrp). These forms are assumed to be the infectious entity. However, the detailed molecular characteristics of PASrps remain unclear. Here, we identified a novel polymycovirus, Penicillium janthinellum polymycovirus 1 (PjPmV1), and characterized its purified fraction form in detail. The PjPmV1 had five dsRNA segments associated with PASrp.Density gradient ultracentrifugation of the PASrp-associated PjPmV1 dsRNA revealed its uneven structure and a broad fractionation profile distinct from that of typical encapsidated viruses.Moreover, PjPmV1-PASrp interacted in vitro with various nucleic acids in a sequence-nonspecific manner. These PjPmV1 features are discussed in view of the diversification of genomic segment numbers of the genus Polymycovirus.